Low dose penicillamine in systemic sclerosis: is it effective? - Farah Sameem; Iffat Hassan; Imran Majid; Qazi Masood (Our Dermatology Online, 2012)
Low dose D-penicillamine 150mg was given on alternate days to 23 patients of limited cutaneous systemic sclerosis (lcSSC) and 5 of diffuse cutaneous systemic sclerosis (dcSSC) subtypes. Modified Rodnan scoring remained unchanged in 19 and progressed in 3 patients of lcSSc. Only 1 female showed a decrease in the score. In the dcSSc, score decreased only in 1. She had a baseline score of 12 which went down to 4. No new systemic activity was seen in her.